Toxicidad aguda in vitro frente a nauplios de Artemia franciscana y actividad antiinflamatoria in vitro de tres especies vegetales Amazónicas sobre eritrocitos plasmáticos - Lopez Alama, Doris Lorena (2024)
In daily life, it is of special interest to study plant species with ethnomedicinal properties, allowing to guarantee their safety and security in the use of different organs (leaves, bark, among others). The study allowed the evaluation of acute in vitro toxicity against Artemia franciscana nauplii and in vitro anti inflammatory activity of Cecropia strigosa Trécul (cetico) bark, Piper aduncum L. (matico) and Mansoa alliacea Lam (ajos sacha) leaves on plasma erythrocytes. Samples selected and collected for convenience, processed and tested at concentrations of 10, 100, 1000 and 1500 ppm. According to the acute toxicity results, the highest amount of dead nauplii is found in the hydroalcoholic extract of M. alliacea Lam - leaves at 10 ppm, according to Table 1; according to table 2, all the extracts evaluated have a CL50 > 1500 ppm. Table 5, C. strigosa Trecul - bark obtained the highest % inhibition among the other plant species. Furthermore, each of them exhibits an IC50 > 1500 ppm. These findings allow us to conclude that none of the extracts tested exhibited acute toxicity and anti-inflammatory activity at the concentrations evaluated.